Patient advocacy in head and neck cancer: Realities, challenges and the role of the multi‐disciplinary team. (6th February 2020) - Dawson, Camilla; Roe, Justin; Starmer, Heather; Brady, Grainne; Nund, Rebecca; Coffey, Margaret; Govender, Roganie; Patterson, Jo M.; Nankivell, Paul; Topping, Annie; Sharma, Neil; Parmar, Sat; et al.
Abstract: This paper explores the concept of advocacy in head and neck cancer. We define inherent challenges in the development and success of advocacy within this context and offer ways to embed it within clinical practice. We outline what advocacy is, ways in which it may benefit people with head and neck cancer and the engagement required from healthcare professionals to facilitate advocacy to improve outcomes.